O2 An epidemiological analysis of men who have sex with men (msm) who are prescribed hiv post-exposure prophylaxis: implications for wider pre-exposure prophylaxis policy. (18th May 2015) - Mitchell, Holly; Furegato, Martina; Hughes, Gwenda; Field, Nigel; Mohammed, Hamish; Nardone, Anthony
Abstract : Background/introduction: Post-exposure prophylaxis following sexual exposure (PEPSE) is a potential method of preventing HIV infection in certain circumstances. Initiation of PEPSE is recommended following receptive anal intercourse with a partner of known positive or unknown HIV status from a high risk group. Aim(s)/objectives: To investigate the characteristics and risk profile of patients receiving PEPSE to determine whether this could inform development of pre-exposure prophylaxis (PrEP) policy for men who have sex with men (MSM). Methods: Data from the Genitourinary Medicine Clinic Activity Dataset (GUMCADv2) were used to investigate the characteristics of patients receiving PEPSE. Associations with PEPSE use were assessed using multivariate logistic regression. Results: Between 2011 and 2013, 14, 118 patients received PEPSE, of which 63% (8, 896) were MSM. Among MSM receiving PEPSE, 14% (1, 213) received more than one course (maximum 13 courses), 45% (3, 990) were aged 25–34 years and 75% (6, 702) were of white ethnicity. 2.0% were diagnosed with HIV between 4 and 16 months after receiving their last course of PEPSE. Compared to MSM controls not receiving PEPSE, MSM receiving PEPSE were significantly more likely to be of non-white ethnicity (adjusted OR = 1.28, 95% CI 1.21–1.36), and to be diagnosed with HIV following a subsequent exposure (adjusted OR = 1.21, 95% CI 1.03–1.41). Discussion/conclusion: MSM prescribed PEPSE are at high risk of acquiring HIV infection following a subsequent exposure and may require intensive interventions to ensure course completion and reduce HIV risk behaviour. PrEP may be beneficial for high-risk MSM receiving PEPSE and also avoid the need for repeat PEPSE prescriptions.